2010 IEEE/RSJ International Conference on Intelligent Robots and Systems 2010
DOI: 10.1109/iros.2010.5649009
|View full text |Cite
|
Sign up to set email alerts
|

Local optimization of cooperative robot movements for guiding and regrouping people in a guiding mission

Abstract: Abstract-This article presents a novel approach for optimizing locally the work of cooperative robots and obtaining the minimum displacement of humans in a guiding people mission. Unlike other methods, we consider situations where individuals can move freely and can escape from the formation, moreover they must be regrouped by multiple mobile robots working cooperatively. The problem is addressed by introducing a "Discrete Time Motion" model (DTM) and a new cost function that minimizes the work required by rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Next we would like to use a smarter prediction of the person's path, instead of a random movement [5]. Furthermore the adaptive method could be improved by giving preference to close search locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Next we would like to use a smarter prediction of the person's path, instead of a random movement [5]. Furthermore the adaptive method could be improved by giving preference to close search locations.…”
Section: Discussionmentioning
confidence: 99%
“…In this way we can do real-time experiments with human volunteers. Moreover, we compare our methods with a previous and well-known system: heuristic person follower [5] Through a large number of synthetic and real experiments, we observed that the Adaptive Highest Belief Continuous Real-time POMCP Follower was able to find and follow different volunteers, while the other two methods performed the task slowly or lost the person, and therefore could not continue the mission.…”
Section: Introductionmentioning
confidence: 98%
“…Computer vision techniques for human-robot interaction have been mainly focused on recognizing people in urban scenarios [10,34,39] as well as identifying human gestures and activities [13,36] to establish contact with people and perform particular robotics tasks such as guiding people in museums and urban areas [18,42,49], providing information in shopping malls [23], or recognizing human emotions through classifying facial gestures [9]. Although these techniques have endowed the robot with remarkable interaction skills, they are commonly computed offline and using a potentially large training time.…”
Section: Human-robot Interactionmentioning
confidence: 99%
“…In a previous work (Garrell and Sanfeliu, 2010a), we studied how robots should behave when they accompany groups of people, or which strategy the group of robots should follow when a person moves away. In this work, we go one step further, presenting a model designed to prevent people from moving away from the formation.…”
Section: Prediction and Anticipation Modelmentioning
confidence: 99%
“…The results, a discussion of the methods used and conclusions are presented in Sections 8, 9 and 10 respectively. This paper is an expanded version of the work presented in (Garrell and Sanfeliu, 2010a). In this current version we have included a new model called Prediction and Anticipation Model which has been developed to predict human behavior and prevent people from straying from the formation.…”
Section: Introductionmentioning
confidence: 99%